Starch Depletion and Sugars in Developing Cotton Leaves - Chang, Chong W. (1980)
Cotton plants (cv. Coker 100) were exposed to a 14-hour dark period. Starch degradation occurred with no accumulation of sugars due mainly to translocation. Considerable amounts of starch degradation products however were detected from leaves after phloem transport was blocked. A minor component (10 to 25% of total starch) with a linear structure, amylose, was preferentially degraded, whereas the major multiple-branched component (about 80%), amylopectin, showed an increasing resistance to degradation with leaf age. This relationship was also shown by the decreasing iodine-binding capacity of unit starch with increasing leaf age. The structural resistance of amylopectin to enzymic dark degradation was one of the barriers to starch dissolution in cotton.